Screening and identification of host signaling pathways for alleviating influenza-induced production of pro-inflammatory cytokines, IP-10, IL-8, and MCP-1, using a U937 cell-based influenza model - Chen, Si; Yu, Yang; Su, Yue; Lian, Xiaoqin; Jiang, Lefang; Li, Zhuogang; Zhang, Mingxin; Gao, Yarou; Zhang, Haonan; Zhu, Xingjian; Ke, Jiaxin; Chen, Xulin (Frontiers in Microbiology, 2025)
Influenza virus infection initiates an exaggerated inflammatory response, which may culminate in a fatal cytokine storm characterized by the excessive production of pro-inflammatory cytokines. Prior research indicates that IP-10, IL-8, and MCP-1, primarily produced by monocytes and macrophages, play a crucial role in influenza-induced inflammation. The lung injury from influenza virus infection can be mitigated by suppressing or inhibiting these cytokines through knockout, knockdown, or targeted intervention approaches. To identify the key host signaling pathways responsible for producing pro-inflammatory cytokines, we utilized a U937 cell model that secretes IP-10, IL-8, and MCP-1 in response to influenza infection. This model has been previously validated in our laboratory as an appropriate system for screening anti-inflammatory agents and potential drug targets. We conducted a screening assay employing an inhibitor library consisting of 2,138 compounds that target various known pathways and host factors. Our findings indicated that inhibitors targeting protein tyrosine kinases and mitogen-activated protein kinases demonstrated superior efficacy in suppressing cytokine production induced by influenza A virus infection compared to inhibitors aimed at other host factors. Notably, a substantial proportion of the identified hits capable of inhibiting the expression of all three cytokines in the secondary screening were classified as tyrosine kinase inhibitors. Validation experiments further established that Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathways, along with p38 MAPK and Raf–MEK–ERK pathways, are the principal regulators of pro-inflammatory cytokine expression in monocytes and macrophages. Moreover, our results suggest that TKIs present promising opportunities as novel therapeutic agents against influenza-induced pneumonia.